TINJAUAN TEBAL PERKERASAN PADA RUAS JALAN MARISA-MOTOLOHU IV KABUPATEN POHUWATO - Gobel, Erna; Rachman, Ari Putra (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2024)
Review of Pavement Thickness on Marisa Motolohu IV Road Section, Pohuwato Regency Marisa – Motolohu IV Road is a collector road which is a very useful transportation in the community and a road to agropolitan access in Pohuwato Regency, Gorontalo Province. In improving the road, adequate studies are needed to achieve optimal benefits. Road pavement thickness planning uses the SNI/AASHTO 93 method. Traffic enumeration surveys are carried out on road sections located in the study area. Subgrade research to find representative CBR values. In this planning stage, the criteria considered in this planning are traffic volume, time limits, traffic loads, reliability, environmental conditions, road performance criteria, drainage factors. Field conditions (existing) on ​​the Marisa – Motolohu IV section are (D1) 5.0 cm, base layer (D2) 10.0 cm, subbase layer (D3) 15 cm. The results of the study obtained the thickness of each pavement, namely: surface layer (D1) 8.0 cm, upper foundation layer (D2) 13 cm, lower foundation layer (D3) 19 cm. This study can be used as a comparison in previous planning using different methods.